Evidence of a second nursery area of the sandbar shark, Carcharhinus plumbeus (Nardo, 1827) in the Eastern Mediterranean Sea - Basusta, Nuri; Basusta, Asiye; Ozyurt, Caner E. (Natl Centre Marine Research, 2021)
The sandbar shark (Carcharhinus plumbeus) is a large coastal shark species with a cosmopolitan distribution; it has been listed as Endangered in the Mediterranean Sea and Vulnerable for the rest of the world on the IUCN Red List of threatened species. The Gokova's Boncuk Cove in south-western Turkey and the Gulf of Gabes in southern Tunisia are the only known nursery area for the Mediterranean population. On the 24 - 27 July 2017, eight specimens of sandbar sharks, four males, and four females, were accidentally caught at a depth of 7 to 9 m by a pelagic bluefish longline off the coast of Yumurtalik Bight in the Gulf of Iskenderun. The total lengths and weights of males and females were 54.5 - 61.0 cm, 930 - 1,484 g, and 49.6 - 62.4 cm, 918 - 1,568 g, respectively. They all had unhealed umbilical scars that were still open as a narrow slit, measuring 4.35 and 5.39 mm in length. This study provides a record of the neonate sandbar sharks from the Yumurtalik Bight. Consequently, this occurrence represents that this area of the north-eastern Mediterranean Sea may be a second breeding and nursery grounds for this species after the Boncuk Cove in Gokova Bay in Turkey.
Keywords: Boncuk cove; bycatch; Carcharhinidae; nursery area; neonates; Yumurtalik Bight